Development of an Islamic Religious Mentoring System (SIMA'I) based on a Mobile Application System Using the ADDIE Model - Mohammad Muspawi; Muhammad Sobri; Ady Muh. Zainul Mustofa; Salman Hasani; Abdulloh Alusamah (State Islamic Institute of Madura, 2024)
This research aims to develop a mobile application to make tutors and students in Jambi University easier to fulfill Islamic religious tutorial assignments. Research and Development with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model is used as the basis for the method with the main focus of this applied research on Application Design and the Effectiveness of its Implementation in the Islamic Education tutorial program. The result of this research is the development of a mobile application called SIMA'I (Islamic Religious Mentoring Information System) that is a new idea for Islamic Religious Learning innovation based on the Mobile Application System which is designed for tutors and students to fulfill Islamic religious tutoring tasks which up to now are still manual. The results of the questionnaire showed that on a scale of 1 to 5, SIMA'I obtained an average performance of 4.17 on the effectiveness of tutorial implementation and an average of 4.88 on the efficiency of the tutorial program, thus showing a positive effect on the Islamic tutorial program at Jambi University. SIMA'I scored high on the components of